BIMBINGAN BELAJAR BAHASA INGGRIS BAGI ANAK-ANAK SDN 02 NAGARI PULAURAJO KECAMATAN AIRPURA - Hartono, Rodi; Pahrizal, Novri; Pardisa, Marcelia Puti (Institut Agama Islam Negeri Kerinci, 2021)
The tutoring program exists to provide English tutoring for children at Elementary Scholl Number 02 Nagari Pulaurajo, Airpura District, as a strategy to improve English communication quality. The aim of English tutoring is for children to have an introduction to primary English material and to be able to pronounce essential words and sentences in English that are related to everyday life. The method for implementing Community Service regarding English language tutoring for children at Elementary Scholl Number 02 Nagari Pulaurajo, Airpura District, is the socialization, training, and guidance methods. The results of the service activities show that the children are thrilled and interested in the English language tutoring program. The children had difficulty pronouncing English words at the beginning of the English tutoring meeting. After the third meeting, the children started to pronounce words correctly, even though some participants still pronounced them wrong. Guidance methods used to guide and train children are playing, singing, spelling, pronouncing, and role playing. The learning results of children at Elementary Scholl Number 02 Nagari Pulaurajo, Airpura District, before tutoring showed that only 1 elementary school child who took the test passed while 19 children did not. The overall average score is 57. This indicates that children need to take English language tutoring. The results of the test carried out after the English language tutoring was carried out showed that the children of Elementary Scholl Number 02 Nagari Pulaurajo, Airpura District, who took the test all passed the test.